LITERATURE REVIEW: INTEGRASI KEARIFAN LOKAL DALAM LEMBAR KEJA PESERTA DIDIK (LKPD) IPA TERHADAP MINAT DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Nihayati, Zaizatun; Wasino; Avrilianda, Decky; Ellianawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the integration of local wisdom in science student worksheets for elementary schools. The method used is Systematic Literature Review (SLR) with the stages of collection, selection, analysis, and synthesis. Literature was sourced from Google Scholar, Semantic Scholar, Cross ref, and OpenAlex with a journal range of the last 5 years (2021-2025). Data were analyzed with Publish or Perish (PoP) and VOSviewer to map research trends. A total of 12 articles were reviewed based on inclusion and exclusion criteria. Findings show that local wisdom-based science worksheets can enhance students’ interest and learning outcomes.